Quality of life and glycaemic control among older population with diabetes in three districts of Peninsular Malaysia - Shalihin, Mohd Shaiful Ehsan; Ahmad Zubaidi, Zati Sabrina; Basri, Hassan; Md Aris, Mohd Aznan; Omar, Ahmad Marzuki; Mohammad Aidid, Edre (2023)
The older population is increasing in numbers worldwide. Most of them have multiple comorbidities including diabetes. Diabetic control in elderly is usually challenging. Their quality of life and socioeconomic condition either in rural or urban area could affect their disease progress. This study aims to measure the diabetic control and its associated factors, including quality of life among the older population with diabetes in three different districts of Malaysia.